An analysis of Central America and Eastern Europe Revealed Comparative Advantages - Gutierrez, Mauricio Garita; Godinez, Jose (Journal of Eastern European and Central Asian Research (JEECAR), 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--> <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The present study applies the revealed comparative advantages through the Balassa Index to determine the comparative advantages, disadvantages, and intra-product commerce tendencies between Central America and Eastern Europe with the purpose of determining the possibility of a free trade agreement for Central America. The approach of the study is through the connection between the European Economic Union and the Central American Common market, which shares a common background and relates them to research of Bela Balassa (1965) to determine how commerce between Central America and Eastern Europe has performed and the possibilities of growth that this commerce has through a free trade agreement. The study demonstrates the importance of analyzing competitive advantages. This paper presents the difference in competitive advantage between Eastern Europe and Central American establishing the benefits when negotiating a free trade agreement between both economic blocks. Therefore, analyzing and negotiating between products of competitive advantages may lead to a more sustainable economic growth.